Advances in biofeedstocks and biofuels. Volume 1, - Singh, Lalit Kumar; Chaudhary, Gaurav (John Wiley & Sons ; Scrivener Publishing, 2016)
A collection of papers from some of the worlds foremost authorities on biofeedstocks and biofuels, this book covers biofeedstocks and how they are processed, and is a must-read for any engineer, scientist, technician, or student working in this.
Keywords: Biomass energy.; elektronické knihy; electronic books